The Interaction between Public Sector Wage, Inflation and Exchange Rate Volatility in Ghana - Ofori-Abebrese, Grace; Pickson, Robert Becker; Azumah, George Kwesi Walanyo (Scientific Research, 2017)
Continuous depreciation of the cedi has been in the orbit of concern of policy makers for time immemorial. This is because, in spite of many policy actions to restore the continuous depreciation of the cedi amidst wage hikes and inflation, the efforts of policy makers seem to thwart in vain. The ARDL method was empirically used to determine whether the rising public sector wage bill and inflation have any impact on the value of the cedi over the period 1986 to 2014. The study discovered that inflation, money supply, interest rate and public wage bill have significant impact on exchange rate in the Ghanaian economy. The outcome of this study postulated that exchange rate determination in Ghana is also a fiscal phenomenon in spite of the significant and domineering role played by monetary expansion. Based on this information, the paper proposed that equal attention must be accorded both fiscal and monetary policy in exchange rate stabilization. It, therefore, suggested that there must be a purely independent central bank; devoid of political appointments and interference to carry out its mandate with free hands. An independent non-political fiscal body like the monetary policy committee under Bank of Ghana must also be established under the same body independent of the Ministry of Finance to ensure wage sustainability through the negotiation of public sector wage adjustment subject to budgetary constraints.
Keywords: Public Sector Wage Bill; Inflation; Exchange Rate; Government Fiscal Deficit; Money Supply